2022
DOI: 10.3389/fendo.2022.812475
|View full text |Cite
|
Sign up to set email alerts
|

Value of Contrast-Enhanced Ultrasound for Evaluation of Cervical Lymph Node Metastasis in Papillary Thyroid Carcinoma

Abstract: The aim of the study was to evaluate the diagnostic value of contrast-enhanced ultrasound (CEUS) in distinguishing between benign and malignant cervical lymph nodes (LNs) in patients with papillary thyroid carcinoma (PTC). Two hundred and one cervical LNs (157 metastatic from PTC and 44 benign) were evaluated using conventional ultrasonography (US) and CEUS before biopsy or surgery. Histopathology was used as the gold standard. We evaluated the size, long axis/short axis ratio (L/S), fatty hilum, hyper-echogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 25 publications
3
17
1
Order By: Relevance
“…According to the clinical guidelines, metastatic cervical lymph nodes often show a round shape, the absence of a fatty hilum, hyperechogenicity, microcalcifications, and cystic changes ( 6 , 34 ). In this study, metastatic CCLNs with a round shape (L/S <2) were found in 76.8% of malignant CCLNs and 50.8% of benign CCLNs, providing a sensitivity of 76.8% and a specificity of 49.2%, whose sensitivity was much higher than that of 37.0%–44.6% and the sensitivity was much lower than that of 70.0%–72.7% in the reported literature ( 6 , 20 , 34 ). This result indicates that lymph nodes of a round shape are more frequently imaged in the central cervical compartment than in the lateral cervical compartment.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…According to the clinical guidelines, metastatic cervical lymph nodes often show a round shape, the absence of a fatty hilum, hyperechogenicity, microcalcifications, and cystic changes ( 6 , 34 ). In this study, metastatic CCLNs with a round shape (L/S <2) were found in 76.8% of malignant CCLNs and 50.8% of benign CCLNs, providing a sensitivity of 76.8% and a specificity of 49.2%, whose sensitivity was much higher than that of 37.0%–44.6% and the sensitivity was much lower than that of 70.0%–72.7% in the reported literature ( 6 , 20 , 34 ). This result indicates that lymph nodes of a round shape are more frequently imaged in the central cervical compartment than in the lateral cervical compartment.…”
Section: Discussionmentioning
confidence: 50%
“…Otherwise, more than half of the patients included in this study had Hashimoto’s thyroiditis, especially in the benign CCLN group, which is usually accompanied by swollen lymph nodes in the central compartment. A fatty hilum was absent in 97.4% of the malignant CCLNs and in 86.9% of the benign CCLNs, providing a sensitivity of 97.4% and a specificity of 13.1%, whose sensitivity was close to that of 91.1%–99.5% ( 19 , 20 , 34 ), and the sensitivity was much lower than that of 22.7%–51.0% reported in the literature ( 19 , 20 ). This result may contribute to the selection bias of many patients with Hashimoto’s thyroiditis included in this study.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…CEUS can show the changes of microvessels after thermal ablation and has become an effective method to evaluate local control of the tumor ( 34 , 35 ). It is of great significance to evaluate the local treatment effect as soon as possible after thermal ablation treatment, especially when the LNM is large or close to important tissues, so as to find the residual tumor tissue in time and carry out re-ablation treatment ( 11 , 25 , 31 , 36 ).…”
Section: Discussionmentioning
confidence: 99%